A network meta-analysis of probiotics in the treatment of childhood asthma - Sun, Jiajia; Zhu, Meiyi; Liu, Ying; Zhang, Di (Frontiers in Pediatrics, 2025)
ObjectiveThis network meta-analysis aims to explore the efficacy and safety of probiotics in children with asthma and attempts to determine which probiotics are most effective in improving outcomes in children with asthma by ranking methods.MethodsA systematic search of Chinese and English databases, including China National Knowledge Infrastructure, Wanfang, VIP, PubMed, and Web of Science, was conducted from the establishment of the databases until July 2024 to screen for randomized controlled trials (RCTs) of probiotics in the treatment of childhood asthma. Lung function was used as the primary outcome measure, and secondary outcome measures included the total clinical response rate, recurrence rate, immune factors, cytokines, and Childhood Asthma Control Test (C-ACT) score. Data processing and analysis were performed using RevMan 5.4 and Stata 17.0 software.ResultsA total of 34 RCTs were included, involving 3,839 participants and 13 interventions. Our analysis showed that conventional treatment combined with probiotics improved outcome indicators in children with asthma better than conventional treatment. Conventional treatment combined with Bifidobacterium–Lactobacillus triplex live bacteria had the highest probability of being the optimal intervention in terms of increasing FEV1% and recurrence rate. Conventional treatment combined with Bifidobacterium adolescentis had the highest probability of being the optimal intervention in increasing FEV1. Conventional treatment combined with Lactobacillus tablets had the highest probability of being the optimal intervention in increasing peak expiratory flow. Conventional treatment combined with Bacillus subtilis diplex live bacteria had the highest probability of being the optimal intervention in improving the total clinical response rate. Conventional treatment combined with Bifidobacterium quadruplex live bacteria had the highest probability of being the optimal intervention in reducing IL-4 and IL-33. Conventional treatment combined with Bifidobacterium triplex live bacteria had the highest probability of being the optimal intervention in improving the C-ACT score.ConclusionProbiotics are effective in treating childhood asthma, and the therapeutic effect of conventional treatment combined with probiotics is superior to that of conventional treatment alone. Therefore, probiotics can be selected as appropriate in the clinical treatment of childhood asthma. However, the overall quality of the evidence was at most low or moderate, suggesting that the certainty of the evidence for probiotics in treating childhood asthma was low.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, PROSPERO CRD42024617940.